Phase I/II trial of palbociclib, pembrolizumab and letrozole in patients with hormone receptor-positive metastatic breast cancer. (September 2021) - Yuan, Yuan; Lee, Jin Sun; Yost, Susan E.; Frankel, Paul H.; Ruel, Christopher; Egelston, Colt A.; Guo, Weihua; Padam, Simran; Tang, Aileen; Martinez, Norma; Schmolze, Daniel; Presant, Cary; et al.
Abstract: Background: CDK4/6 inhibitors modulate immune response in breast cancer. This phase I/II trial was designed to test the safety and efficacy of palbociclib, pembrolizumab and letrozole in women with hormone receptor positive (HR + ) human epidermal growth factor receptor 2 negative (HER2 − ) metastatic breast cancer (MBC). Patients and methods: Women with stage IV HR + HER2 − MBC were enrolled and treated with palbociclib, pembrolizumab and letrozole. Primary end-points were safety, tolerability and efficacy. Results: Between November 2016 and July 2020, 23 patients were enrolled with 20 evaluable for response, including 4 patients in cohort 1 and 16 patients in cohort 2. Cohort 1 median age was 48 years (33–70) and cohort 2 median age was 55 (37–75). Cohort 1 closed early due to limited accrual. Grade III–IV adverse events were neutropenia (83%), leucopaenia (65%), thrombocytopenia (17%) and elevated liver enzymes (17%). In cohort 1, 50% achieved a partial response (PR) and 50% had stable disease (SD). In cohort 2, 31% achieved complete response (CR), 25% had PR and 31% had SD by Response Evaluation Criteria in Solid Tumours version 1.1. Median progression-free survival was 25.2 months (95% confidence interval [CI] 5.3, not reached) and median overall survival was 36.9 months (95% CI 36.9, not reached) in cohort 2 with a median follow-up of 24.8 months (95% CI 17.1, not reached). A correlative immune biomarker analysis was published separately. Conclusion: The combination of palbociclib, pembrolizumab and letrozole is well tolerated, and a complete response rate of 31% was identified in HR + MBC patients who received this combination as front-line therapy. Confirmatory trials are required to better understand the immune-priming effects of CDK4/6 inhibitors. Highlights: Palbociclib, pembrolizumab and AI are safe in HR + metastatic BC patients. Median PFS is 25.2 months. Combination has a CR rate of 31% in HR + metastatic BC patients.